Alluvial gold mining, conflicts, and state intervention in Peru's southern Amazonia - Giraldo Malca, U.F.; Sabogal, A.; Facho Bustamante, N.; Mori Reaño, M.J.; Giraldo Armas, J.M. (Elsevier, 2023)
Artisanal and small-scale mining is one of the most degrading activities in the southern Peruvian Amazonia and its uncontrolled expansion has sparked conflicts over its exploitation, the distribution of profits, and their impacts. To analyze how State actions and other factors have triggered its misgovernment, conflicts, and environmental degradation, we constructed a chronology of events related to territorial occupation, gold exploitation, conflict evolution, and state intervention. The overlapping rights that the government assigns to the territory is one of the most controversial actions. For this reason the spatial distribution of mining, forestry, conservation, and property rights was analyzed using QGIS software. As results, we identified places with up to four rights or uses assigned by government institutions and state interventions that compound informality and chaos in the area. We conclude that the main causes of conflicts and misrule stem from weak state, evidenced by deficient services provided, the concession of incompatible usage rights over a single territory, and the enactment of regulations for purposes other than the public good. Finally, mining formalization has not been successful, because formality does not offer major advantages to the miners, being costly and bureaucratic, while informality is not an inconvenience for miners.
Keywords: Social & Environmental Impacts; Mercury Emissions; https://purl.org/pe-repo/ocde/ford#1.05.08